2005
DOI: 10.1111/j.1365-2303.2005.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA extraction from cervical cells collected in PreservCyt solution for the amplification of Chlamydia trachomatis

Abstract: Objective:  The aim of this study was to compare and evaluate three methods of DNA extraction for the amplification of Chlamydia trachomatis in uterine cervical samples collected in PreservCyt solution. ThinPrep is the trade name for the slide preparation. Methods:  Thirty‐eight samples collected in LCx buffer medium, which were identified as C. trachomatis infected by ligase chain reaction (LCR), were selected for this study. DNA from the PreservCyt samples was extracted by three methods: (i) QIAamp kit, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The SurePath TM fixative should diminish (if not eliminate) proteolytic degradation. Fixative solutions may crosslink proteins and nucleic acids, so as to interfere with proteolytic enzymes and potentially inhibit cellular lysis [33,34]. For our purposes of MS-based proteomics, the “fixative” attribute of the SurePath TM preservative fluid proved to be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…The SurePath TM fixative should diminish (if not eliminate) proteolytic degradation. Fixative solutions may crosslink proteins and nucleic acids, so as to interfere with proteolytic enzymes and potentially inhibit cellular lysis [33,34]. For our purposes of MS-based proteomics, the “fixative” attribute of the SurePath TM preservative fluid proved to be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…BD SurePath and Hologic PreservCyt media are both alcohol-based preservatives and are designed to fix cellular and subcellular components and aid in the cytological evaluation of the obtained smears. Fixative solutions can prove problematic for downstream molecular extraction methods because of the potential to inhibit cellular lysis, because of the potential to interfere with the proteolytic enzymes used in this process, or due to cross-linking of nucleic acids and proteins (5,6). Some prior studies have reported poor recovery of nucleic acids from SurePath and PreservCyt media and inferred that the DNA had degraded over time during storage (7-10).…”
mentioning
confidence: 99%
“…For the majority of the isolates, gDNA was obtained directly by heat shock methods (24). A tip of the biomass pellet was picked using sterile toothpicks, placed in 50 l Tris-EDTA buffer, and subjected to heating at 95°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%